52‐2: Invited Paper: A New 0.64″ 720p OLED Microdisplay for Application in Industrial See‐Through AR HMD. Issue 1 (29th May 2019) - Wartenberg, Philipp; Richter, Bernd; Brenner, Stephan; Rolle, Martin; Bunk, Gerd; Ulbricht, Steffen; Baumgarten, Judith; Schmidt, Christian; Schober, Matthias; Vogel, Uwe
Abstract : This paper discusses different use‐cases for data glasses as well as their impact on the used display. This includes the discussion of a new 0.64‐in 720p OLED microdisplay for AR see‐through head‐mounted display (ST‐HMD) which features 1, 280 × 720 resolution at a pixel pitch of 11um with four subpixels and 8bit per color. For low latency, an adequate high frame rate has been targeted. To reduce motion blur, a "rolling emit" has been implemented.